Factors influencing passengers’ choice of transport mode to Warsaw Chopin Airport - Górecka Aleksandra (Logistics & Sustainable Transport, 2016)
Airport accessibility is an important factor for airport choice and therefore also for airport competition. When air passengers choose an itinerary, they reflect on the transport chain from door to door. Therefore, factors affecting the traveller’s decision for a particular option go beyond the price and quality of air services from airport to airport. The decision for or against a particular air service and a particular airport is to a certain extent dependent on the accessibility of the airport.